Handbook of research on climate change and the sustainable financial sector - Olarewaju, Odunayo, 1987-; Ganiyu, Idris, 1978- (Advances in finance, accounting, and economics (AFAE) book series., 2021)
"This edited book presents a variety of chapters on many evident impacts of climate change on various sectors of the world economy, especially the financial sector which is seen as a specific qualitative predictor of the potential socio-economic effects of climate change"--